Relationship Between Thromboembolic Complications and Intensity of Treatment During Long-Term Prophylaxis with Oral Anticoagulants Following DVT - Schulman, Sam; Lockner, Dieter (Thrombosis and Haemostasis, 1985)
The frequency of thromboembolic recurrencies during secondary prophylaxis after DVT was retrospectively studied and related to the intensity of the oral anticoagulation. All patients receiving oral anticoagulation after DVT at our hospital during April 1972 - May 1980 were studied. Treatment was given to 596 patients for 724 thrombotic events for a total of 4450 months. Thirty-six thromboembolic complications, all objectively verified, occurred. Patients with cancer had complications throughout the entire range of anticoagulation. Patients without neoplastic disease (15 events) never had complications below a prothrombin complex level of 27% as assessed with Simplastin A, corresponding to a BCT-ratio of 1.9. This study confirms, that the lower limit of the therapeutic range, determined by the risk of thromboembolic complications, should be set at a Simplastin A-level of approx. 25% corresponding to BCT 2.0.
Keywords: Oral anticoagulation; Deep vein thrombosis; Pulmonary embolism; Complication; Cancer; Therapeutic range; Simplastin A